Improvements in daytime sleepiness and disrupted nighttime sleep with once-nightly sodium oxybate in people with narcolepsy type 1 and type 2: a plain language summary - Yves Dauvilliers; Thomas Roth; Richard Bogan; Michael J Thorpy; Anne Marie Morse; Fèri Ascencion; Jennifer Gudeman (Becaris Publishing Limited, 2024)
What is this summary about? This is a plain language summary of a published article in the journal Sleep. Narcolepsy is a sleep condition that has 2 different subtypes: narcolepsy type 1 and narcolepsy type 2. These are called NT1 and NT2 for short. Sodium oxybate (SXB) is approved to treat excessive daytime sleepiness (EDS) and cataplexy. People with NT1 and NT2 both have EDS, but cataplexy is only present in people with NT1. Limited information is available about how SXB works in people with NT2. This is because previous trials have included only people with NT1 or people with unspecified narcolepsy. For more than 20 years, the only available formulation of this medicine had to be given twice during the night. Many people with narcolepsy find that chronically waking up in the middle of the night for a second dose of SXB is disruptive to themselves or others in their household. People have also reported sleeping through alarm clocks, missing their second dose, and feeling worse the next day. Some people have accidentally taken the second dose too early, putting them at risk for serious adverse effects. These adverse effects may include slow breathing, low blood pressure, or sedation. The US Food and Drug Administration (FDA) approved a medicine called LUMRYZ™ (sodium oxybate) for extended-release oral suspension in May 2023. LUMRYZ is a once-nightly formulation of SXB (ON-SXB for short) and is taken as a single dose before bedtime. This medicine treats EDS and muscle weakness (also known as cataplexy) in people with narcolepsy. A clinical trial called REST-ON studied ON-SXB to find out if it was better at treating narcolepsy symptoms than a medicine with no active ingredients (placebo). This summary describes a study that tested whether ON-SXB was better than placebo at treating narcolepsy symptoms in people with NT1 or NT2. What were the results? This study showed that compared to people who took placebo, people who took ON-SXB were able to stay awake longer during the day, felt less sleepy during the daytime, had less cataplexy, and had more improvements in their symptoms overall than people who took placebo. What do the results mean? ON-SXB has been proven effective for people with NT1 or NT2. Unlike prior formulations of SXB, ON-SXB is taken once at bedtime, without requiring waking up in the middle of the night for a second dose.